Foam and antifoam behavior of PDMS in MDEA-PZ solution in the presence of different degradation products for CO2 absorption process - Ng, Eileen Li Shien; Lau, Kok Keong; Chin, Sim Yee; Lim, Soh Fong (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Absorption is one of the most established techniques to capture CO2 from natural gas and post-combustion processes. Nevertheless, the absorption process frequently suffers from various operational issues, including foaming. The main objective of the current work is to elucidate the effect of degradation product on the foaming behavior in methyldiethanolamine (MDEA) and piperazine (PZ) solution and evaluate the antifoaming performance of polydimethylsiloxane (PDMS) antifoam. The foaming behavior was investigated based on types of degradation product, temperature, and gas flow rate. The presence of glycine, heptanoic acid, hexadecane, and bicine in MDEA-PZ solution cause significant foaming. The presence of hexadecane produced the highest amount of foam, followed by heptanoic acid, glycine and lastly bicine. It was found that increasing the gas flow rate increases foaming tendency and foam stability. Furthermore, increasing temperature increases foaming tendency, but reduces foam stability. Moreover, PDMS antifoam was able to reduce foam formation in the presence of different degradation products and at various temperatures and gas flow rates. It was found that PDMS antifoam works best in the presence of hexadecane with the highest average foam height reduction of 19%. Hence, this work will demonstrate the cause of foaming and the importance of antifoam in reducing its effect.